Neoadjuvant Chemotherapy in Choroid Plexus Carcinoma: Improving Surgical Safety and Resection Outcomes - Mubashirah Sajid Charolia; Fatima Suleman; Muhammad Shahzad Shamim (Journal of the Pakistan Medical Association, 2025)
Choroid plexus carcinoma (CPC) is a rare and highly vascular malignant brain tumour that occurs mainly in children. Complete surgical resection offers the best chance of long-term survival, but this is often difficult due to excessive intraoperative bleeding. Preoperative (neoadjuvant) chemotherapy has been explored as a strategy to shrink the tumour and reduce its vascularity before surgery. In this review, we have summarized the available literature on preoperative chemotherapy in CPC and its effect on surgical outcomes. Reported cases and small series show that platinum- and etoposide-based regimens can decrease tumour size and intraoperative blood loss, allowing safer and more complete resections. However, due to the rarity of CPC and limited data, larger multicentre studies are required to validate these findings and establish standardized treatment protocols. Keywords: Choroid plexus carcinoma, preoperative chemotherapy, neoadjuvant therapy, gross-total resection, surgical outcomes